Usefulness of Serum Calcitonin in Patients with Thyroid Nodules ≤ 1 cm Without an Indication for Fine-Needle Aspiration - Rosario, Pedro Weslley; Mourão, Gabriela Franco; Calsolari, Maria Regina (Hormone and Metabolic Research, 2020)
Fine-needle aspiration (FNA) is not necessary in adults with nodules ≤ 1 cm without apparent extrathyroidal extension (ETE) or lymph node (LN) involvement on ultrasonography (US). In the absence of FNA and serum calcitonin (Ctn) measurement, medullary thyroid microcarcinomas (microMTC) are not diagnosed. The aim of this prospective study was to evaluate Ctn levels in adults with a low clinical risk of MTC and nodules ≤ 1 cm without ETE or LN involvement on US. A total of 506 consecutively seen adults who had nodules with two or more suspicious features were included. Patients with elevated basal Ctn underwent a calcium stimulation test and FNA. Basal Ctn was normal in 490 patients (96.8%). In the 16 patients with elevated basal Ctn, FNA revealed MTC in only one patient and MTC was not suspected in the 15 patients with elevated basal Ctn. Three patients with stimulated Ctn<100 pg/ml and benign cytology were not submitted to surgery. MTC was excluded by histology in three patients with stimulated Ctn<100 pg/ml and indeterminate or suspicious cytology and in eight patients with stimulated Ctn>100 pg/ml. One patient with stimulated Ctn>100 pg/ml had MTC. Ctn was undetectable 6 months after surgery in two patients with MTC. Although uncommon, even subjects without a suspicious history and with nodules ≤ 1 cm without ETE or LN involvement on US, but with suspicious findings, can have microMTC. The measurement of Ctn permits the diagnosis of these cases.
Keywords: thyroid nodule; microcarcinoma; medullary thyroid carcinoma; serum calcitonin; fine-needle aspiration